Properties of Concrete Containing Rubber Ash and Rubber Crumb as Partial Replacement of Sand - Shahiron Shahidan, Sajjad Ali Mangi, Mohamad Syamir Senin, Sharifah Salwa Mohd Zuki, Mustaqqim Abd Rahim (International Journal of Advanced Science and Technology, 2020)
Tyres waste has been given serious attention because it creates major environmental problems nowadays. In order to decrease the use of natural resources, this study consider rubber ash and rubber crumb as a potential replacement material in concrete production. However, earlier research also suggested to use rubber ash and crumb as a cementitious material or as aggregates in order to reduce the depletion in natural resources. Therefore, this study aims to determine the properties of concrete containing crumb rubber and rubber ash in several percentages and to evaluate the optimum percentage of crumb rubber and rubber ash in concrete. In this study, rubber ash and rubber crumbs were used as fine aggregate replacement in concrete. From the slump test, it was observed that a reduction in workability was due to the size of rubber particles. After a curing period of 28 days, it was found that 7% of rubber ash replacement achieved the highest tensile strength value which is 3.13 MPa or 4% more than normal concrete. For rubber crumbs, the maximum tensile strength value achieved was 3.06 MPa at 3% replacement. Although there was 9% of rubber ash and rubber crumbs inside the concrete, that there was no carbonation detected. The modulus of elasticity test showed that for RAC, the value increased due to the increment in rubber ash replacement percentage. However, the modulus of elasticity for RCC decreased due to the increment in rubber crumb replacement percentage. This clearly showed that the smaller the size of the rubber particles, the higher the elasticity value. Overall, the optimum value in terms of tensile strength and modulus of elasticity was achieved by 7% replacement for rubber ash and 3% replacement for rubber crumbs. From this study, it can be concluded that rubber ash and rubber crumbs provide a great opportunity to be used as fine aggregates in concrete.